Kontribusi dalam Upaya Peningkatan Motivasi Belajar Siswa di TPQ Desa Padang Pelawi - Rizki Ramadhan; Ermala Aweni; Riki Rikardo; Sucita Ayu Rahmadia; Livia Susanti (MENYALA: Jurnal Pengabdian Masyarakat, 2024)
This research discusses the contribution and role of Real Work Lecture (KKN) students at UIN Fatmawati Sukarno Bengkulu in increasing student learning motivation at the Al-Qur'an Education Park (TPQ) Padang Pelawi Village. This KKN program applies creative and interactive teaching methods, which have succeeded in increasing students' interest and enthusiasm in learning the Koran. The presence of students who are closer to the student's age helps create a more conducive learning environment and encourages students to participate more in learning activities. Apart from that, KKN students also participate in developing students' social skills. However, this research also found challenges in maintaining the learning methods that had been implemented after the KKN program ended. For this reason, continuous support is needed from community training and for TPQ teachers so that the positive impacts that have been achieved can continue to be felt in the long term. Thus, the contribution of KKN students in increasing student learning motivation at TPQ Padang Pelawi Village is very significant, but needs to be supported by lasting efforts.